211k views
3 votes
Type the correct answer in the box. Use numerals instead of words. If necessary, use / for the fraction bar.

Write the expression in simplest form.
(-+ 3) - 2 (-x) =

User Mwspencer
by
6.6k points

2 Answers

3 votes

Answer:

Simplest form of expression:

-3+2x

User OptimusCrime
by
6.2k points
6 votes

Answer:

2x - 3 (or) -3 + 2x

Explanation:

Given equation,

→ (-+ 3) - 2 (-x)

The simplest form will be,

→ (-+ 3) - 2 (-x)

→ -3 + (-2 × -x)

→ -3 + 2x

→ 2x - 3

Thus, the answer is 2x - 3.

User SorryMike
by
5.9k points